More 5-minute princess stories - Bergen, Lara.; Walt Disney Enterprises (New York : Disney, 2003)
This collection contains five brand-new stories about everyone's favorite Disney Princesses: Ariel, Jasmine, Belle, Snow White, and Sleeping Beauty. Filled with romance, glamour, adventure, and dreams come true, each story can be read in just five minutes. 5 yrs+
Keywords: Princesses -- Juvenile fiction; Fairy tales